Benthic fauna and fish, wave and tidal currents, sediment, anthropogenic impact from Swansea Bay, Wales, UK, 2014 - Ruth Callaway; Iain Fairley; Jose Horrillo-Caraballo (PANGAEA, 2020)
This data was collated for a study where benthic fauna and fish community data were linked with modelled wave and tidal current data, sediment characteristics and anthropogenic impact like dredge spoil disposal and wastewater discharge. The aim of this study was to provide a holistic understanding of the relative importance of anthropogenic and natural variables for macroinfauna, epifauna and fish in a heavily modified waterbody (HMWB) designated under the EU Water Framework Directive (WFD). The study area, Swansea Bay (Wales, UK), had two regularly dredged industrial ports, three estuaries, a wastewater discharge point and a dredge-spoil disposal site. Wave and tidal current models were constructed, and environmental data were gathered by field studies. Biota were assessed by grab sampling and dredging. The study highlighted that ecosystems driven by a strong hydrodynamic regime can be relatively resistant to human activities.